Volatile compounds from organic and conventional passion fruit (Passiflora edulis F. Flavicarpa) pulp - Macoris, Mariana Serrao [UNESP]; Janzantti, Natalia Soares [UNESP]; Garruti, Deborah dos Santos; Monteiro, Magali [UNESP] (Soc Brasileira Ciência Tecnologia Alimentos, 2011)
The volatile compositions from organic and conventional passion fruit pulps produced in Brazil were investigated. The pulps were also physicochemically characterized. The volatile compounds from the headspace of the passion fruit pulp were stripped to a Porapak Q trap for 2 hours; they were eluted with 300 mu L of dichloromethane, separated by gas chromatography/flame ionisation detection and identified through gas chromatography/mass spectrometry. Both pulps conformed to the requirements of the Brazilian legislation, indicating they were suitable to be industrialized and consumed. A total of 77 compounds were detected in the headspace of the passion fruit pulps - 60 of which were identified, comprising 91% of the total chromatogram area. The major compounds were the following: ethyl butanoate, 52% and 57% of the total relative area of the chromatogram for the organic and conventional passion fruit pulps, respectively; ethyl hexanoate, 22% and 9%, respectively; and hexyl butanoate, 2% and 5%, respectively. The aroma of the organic passion fruit pulp is mainly related to the following volatile compounds: ethyl hexanoate, methyl hexanoate, beta-myrcene and D-limonene. The conventional passion fruit pulp presented methyl butanoate, butyl acetate, hexanal, 1-butanol, butyl butanoate, trans-3-hexenyl acetate, cis-3-hexen-1-ol, butyl hexanoate, hexyl butanoate, 3-hexenyl butanoate and 3-hexenyl hexanoate as the main volatile compounds for aroma.

A composição de voláteis das polpas de maracujá orgânico e convencional produzido no Brasil foi estudada. As polpas também foram caracterizadas físico-quimicamente. Os compostos voláteis do headspace da polpa de maracujá foram capturados em Porapak Q por 2 horas, aluídos do polímero com 300 µL de diclorometano, separados por cromatografia gasosa/ionização de chama e identificados por cromatografia gasosa/espectrometria de massas. Ambas as polpas estavam de acordo com as exigências da legislação brasileira, indicando que estavam adequadas para a industrialização e consumo. Um total de 77 compostos foi detectado no headspace das polpas de maracujá, dos quais, 60 foram identificados, compreendendo 91% da área total do cromatograma. Os compostos majoritários foram butanoato de etila, com 52% e 57% da área relativa total do cromatograma, nas polpas de maracujá orgânica e convencional, respectivamente; hexanoato de etila, com 22% e 9%, respectivamente; e butanoato de hexila, com 2% e 5%, respectivamente. O aroma da polpa de maracujá orgânico está relacionado principalmente aos compostos voláteis hexanoato de etila, hexanoato de metila, β-mirceno e D-limoneno. Na polpa de maracujá convencional, os compostos voláteis butanoato de metila, acetato de butila, hexanal, 1-butanol, butanoato de butila, acetato de trans-3-hexenila, cis-3-hexen-1-ol, hexanoato de butila, butanoato de hexila, butanoato de 3-hexenila e hexanoato de 3-hexenila foram relacionados ao aroma.
Compostos voláteis da polpa de maracujá (Passiflora edulis F. Flavicarpa) orgânica e convencional
Keywords: organic passion fruit; aroma; flavor chemistry; fruit pulp; gas chromatography/mass spectrometry